PENGAMANAN DATA MENGGUNAKAN EMAIL TERENKRIPSI DI AKADEMI ANGKATAN UDARA - Fahrurozi, Muhammad; Ridho, Mavel; Setiyono, Setiyono (Akademi Angkatan Udara, 2022)
Confidentiality of information and communication to protect sensitive data is an absolute thing and must be fulfilled when this will not exist in the military world. Confidentiality of data in exchanging information will protect institutions from unwanted things. As a military educational institution, the Air Force Academy requires a data security system to guarantee an institution. In securing data, confidentiality and security remain, namely confidentiality, integrity and availability so that the information content is maintained. The rapid development of data security tools, one of which uses the Pretty Good Privacy method. This system uses yahoo RSA cryptographic techniques to protect data sent via email. Several AAU work units that use the PGP method in carrying out e-mail data exchange are the financial unit, the health unit and the personnel unit that manages human resources. This PGP method can protect data or information on email. This technique is expected to be the first step in data security at the Air Force Academy